2009 IEEE International Conference on Software Maintenance 2009
DOI: 10.1109/icsm.2009.5306315
|View full text |Cite
|
Sign up to set email alerts
|

On the use of relevance feedback in IR-based concept location

Abstract: Concept location is a critical activity during

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
107
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(108 citation statements)
references
References 27 publications
1
107
0
Order By: Relevance
“…In [8], Gay et al showed that ERF can assist developers in locating the target file(s) by reformulating the original query iteratively. At each iteration, the reformulated query is submitted and a new set of retrieval results is presented to the user to obtain the next round of feedback.…”
Section: A Explicit Relevance Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…In [8], Gay et al showed that ERF can assist developers in locating the target file(s) by reformulating the original query iteratively. At each iteration, the reformulated query is submitted and a new set of retrieval results is presented to the user to obtain the next round of feedback.…”
Section: A Explicit Relevance Feedbackmentioning
confidence: 99%
“…As it turns out, researchers in the software engineering community have looked at QR in the past -but in a way that either places additional burden on the developer in constructing a query or that are based on general statistical properties of a software library. To elaborate, as an example of QR that places additional burden on the developer, we have the study of Explicit Relevance Feedback (ERF) by Gay et al [8]. They used Rocchio's method for QR to locate a target file by reformulating the original query [9] through an iterative interaction with the user.…”
Section: Introductionmentioning
confidence: 99%
“…Henceforth, we refer to this approach as the batch mode approach. However, this can be time consuming and can lead to high query latency 1 . Alternatively, one could re-compute the index and the model at major releases and ignore commit-level changes (henceforth, we refer to this approach as the limited update).…”
Section: Introductionmentioning
confidence: 99%
“…Effort has also gone into studying and improving the quality of the query to improve retrieval accuracy [1] [7][8] [9] [10]. In other words, research in the area of IR based bug localization has focused primarily on retrieval effectiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation